Gender Equality in Politics (Study on The Indonesian Constitutional Court's Decisions on Judicial Review Related to Women's Political Participation) - Riris Ardhanariswari; Tenang Haryanto; Supriyanto Supriyanto (Jurnal Dinamika Hukum, 2021)
Such conception of human rights is in line with international human rights law, in particular with adopting a comprehensive women's rights instrument, namely the Convention on the Elimination of All Forms Discrimination Against Women, hereinafter referred to as the CEDAW Convention, which was ratified by the State of Indonesia with Law No. 7 of 1984 on Ratification of the CEDAW Convention. Women, especially in Indonesia are still left behind both in public life and politics. This raises the issue of gender equality, which means a condition of "inequality" experienced by women. The current trend in society is that women tend to participate in the national level such as general elections or participation in the DPR or MPR. Currently, there is yet any law that comprehensively regulates the protection of women's rights. Indonesia still rely on legal instruments regarding gender equality with various conventions such as the CEDAW Convention, the ICESCR Convention, and the ICCPR Convention. Women face discrimination, not only in the domestic sector but also in the public sector. Therefore, it is important to learn and develop the multifunctional dynamic character of women. This development has appeared in various Constitutional Court's decisions on judicial review of laws.Keywords: genderequality;judicial reviews;general election